The Study of Mangrove Ecosystems’ Services Valuation in Semarang City - Tito Aditya Perdana; Febrianur Ibnu Fitroh Sukono Putra; Risanda Alirastra Budiantoro (Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
Introduction/Main Objectives: This study estimates how much economic value will be lost from contact activities within the coastal areas in the research location. Background Problems: The area of Semarang City has flood and tidal problems, the damage to the mangrove forests in Semarang City began with the boom in shrimp farming between 1980 and 1990. Hopefully, this valuation can provide an overview of the current health of the ecosystem and become the basis for a mangrove management strategy in the future. Novelty: The novelty of this study is that it uses a sharper satellite (Image Pleades Resolution 0.5 m) to calculate the mangrove area in the research location. Research Methods: This research uses a total economic valuation, an estimation of the mangrove’s carbon stock and heavy metals, the replacement cost to prevent tidal flooding, and the willingness to pay. Findings/Results: We find that the existing economic value in the study area is very large and should be preserved for conservation. Conclusion: The environment cannot produce something instantly, but it needs to be preserved as a balance to nature.